IMPLEMENTASI PEMBELAJARAN JARAK JAUH MELALUI APLIKASI ZOOM BAGI MAHASISWA PENDIDIKAN MASYARAKAT IKIP SILIWANGI - Jenal Arifin; Ansori Ansori; Dinno Mulyono (IKIP Siliwangi, 2021)
During this pandemic we do all kind of activities. Such as work, School, College and all activities that are normally carried out normally, and it can be carried out directly but in fact everything cannot be done directly. In this particular case implementation of the process learning becomes constrained. There fore in utilizing technology distance learning activities are carried out, and it is one of the solution needed by educator and student during a pandemic. Which accurred at the beginning of the month of February 2020. The most obvius technological development at this time is the development of the internet. Even though during a pandemic, learning activities can still carried out even if not directly. The purpose of this research is motivated to determine the utilization and effectiveness of the zoom application. On the quality of student distance learning community education of IKIP Siliwangi the method used is a qualitative approach with descriptive method data collection techniques through observation and interviews.